E marketing for Indonesia Coffee Famer Using UTAUT2 - Faradillah, Yanty; Saany, Syarilla Iryani Ahmad; El-Ebiary, Yousef A Baker (Journal of Technology and Engineering, 2024)
This study investigates the acceptance and usage of e-marketing among Indonesian coffee farmers using the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) model. With the rapid growth of digital platforms, e-marketing offers unique opportunities for coffee farmers to expand their market reach, increase sales, and improve operational efficiency. A qualitative research approach was adopted to explore UTAUT 2, the development of e-marketing for Indonesian coffee farmers can become more effective and relevant because this model helps design strategies based on a deep understanding of the factors that encourage or hinder technology acceptance among farmers. how factors such as performance expectancy, effort expectancy, social influence, and facilitating conditions, impact coffee farmers' adoption of e-marketing technologies. Data were collected through in-depth interviews with coffee farmers and industry stakeholders across several Indonesian regions, providing a comprehensive understanding of the challenges and motivations driving e-marketing adoption. The findings reveal that, while coffee farmers recognize the potential benefits of e-marketing, several barriers—such as limited digital literacy, infrastructure constraints, and concerns over technology costs—hinder widespread adoption. Social influence, particularly from peers and family, was found to play a critical role in encouraging the use of digital platforms. Moreover, facilitating conditions, including access to training and support, significantly enhance adoption rates. This research provides valuable insights for policymakers and technology providers aiming to increase digital inclusion among rural coffee producers. It suggests that tailored interventions addressing local challenges can foster greater e-marketing adoption, ultimately contributing to the economic sustainability of Indonesia's coffee farming sector.